On paracompact Space Using Semi-Open Sets - Naoum, A.G.; Aziz Hussain Al-Abdulla, Raad (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2017)
Abstract. This work consists of two sections. In section one we recall the definitionconcerning semi-open sets. In section two we recall the definition of paracompact space and we introduce similar definition by using semi open sets also we proof some results about it.